Environmental Influences on Young Adult Male Height. A Comparison of Town and Countryside in the Netherlands, 1815-1900 - Jan Kok; Erik Beekink; David Bijsterbosch (Historical Life Course Studies)
The first phase of industrialization has often been associated with decreasing standards of living for workers, and early industrial towns and cities gained bad reputations. One of the best indicators for living conditions in early life is young adult height, and the literature has often pointed at urban-rural differences in heights to illustrate the initial decrease of living standards due to urbanization and industrialization. But how was urban residence connected to height? Causal mechanisms can include disease environment related to crowdedness, food availability or the nature of urban versus rural work. But perhaps urban-rural differences can simply be attributed to compositional effects, e.g. in cities relatively more poor, illiterate or incomplete families were to be found. Another question is whether urban-rural differences are limited to large cities compared to the rest, or whether we also find differences between towns and villages. In this brief, exploratory paper, we combine two detailed local datasets to provide answers to these questions. We contrast an early industrializing town, with a typical proletarian sub-culture of tile bakers and a significant middle class (Woerden in the province of South-Holland) to an agrarian community (the village of Akersloot and surrounding area in the province of North-Holland). Our dataset allows us to disentangle effects of the family composition, the family’s socio-economic status, food prices, and the environment on bodily growth of 1,738 young men. Our results suggest that the specific conditions of urban workers were more important for the physical development of their children than the urban or rural setting itself.